The Impact of Social Reputation Features in Innovation Tournaments: Evidence from a Natural Experiment - Deodhar, Swanand J.; Gupta, Samrat (Information Systems Research, 2023)
With firms increasingly relying on external knowledge resources for solving complex problems, the role of digital platforms, which make this external search efficient, has become significant. For such platforms, of which Kaggle is an example, a perennial challenge is to elicit high-quality solutions from their voluntary contributors. To this end, our work underscores the importance of platform-wide design decisions for the quality of solutions that the platform's users generate. We show that a social feature that offers reputational gain may lead to significant quality improvements. Therefore, we recommend that platforms should view such features more favorably and include them. In addition, our work also suggests that firms that are using digital platforms to engage with external knowledge sources should time their activities, keeping in mind platform-wide design changes given that such changes can directly impact the firm's surplus.